Review: Mekanisme Akumulasi Logam Berat di Ekosistem Pascatambang Timah - Andri Kurniawan; Diah Mustikasari (Jurnal Ilmu Lingkungan, 2019)
Tin exploration and exploitation activities have resulted in damage and changes in ecosystems such as forest damage, changes in soil structure, degradation of soil and water quality, and potential contamination of heavy metals. The changes in macroecosystems also have direct implications for changes in microecosystems. One form of environmental change and ecological impact that is the main concern after tin mining is the presence of heavy metals. Heavy metal accumulation can affect the physical and chemical structure in an ecosystem such as acidity (pH) and high threshold value of heavy metal residues. Extreme physical and chemical conditions, including the presence of heavy metals, affect the biological ability of macro and microorganisms to be able to survive in the environment. This article review aimed to describe the potential contamination of heavy metals such as As, Cr, Cu, Pb, Zn, Fe, and Sn found in post-tin mining locations, heavy metal toxicity, the mechanism of heavy metal accumulation in an organism, and the handling of contamination through physicochemical mechanisms and biology. The results of this review indicated the potential contamination of metal elements found in tin mining locations. These metals can be accumulated directly or indirectly through the food chain, from producers, the lowest consumers, to the highest consumers. Various efforts can be made to deal with metal contamination including (a) physical and chemical (physicochemical) methods such as anion precipitation, electro-winning, electro-coagulation, cementation, reverse osmosis, and electro-dialysis and (b) biological methods such as bioremediation by plants (phytoremediation), fungi (mycoremediation), and bacteria (bacteria bioremediation). The review presented in this paper is expected to be important information in the effort to manage post-mining ecosystems for sustainable and sustainable use and development of the environment.